1994
DOI: 10.1136/ard.53.11.743
|View full text |Cite
|
Sign up to set email alerts
|

Urine neopterin: a new parameter for serial monitoring of disease activity in patients with systemic lupus erythematosus.

Abstract: Objective-To investigate the role of serial measurement of urine neopterin concentration in monitoring the progression of systemic lupus erythematosus (SLE) disease activity scored using the British Isles Lupus Assessment Group (BILAG) index.Methods-We foliowed prospectively 68 unselected SLE patients for a total of 464 patient months during which 233 separate assessments were carried out. At each assessment, urine neopterin, determined by high performance liquid chromatography, together with erythrocyte sedim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 15 publications
0
16
0
1
Order By: Relevance
“…That study did not compare serum neopterin to the blood BeLPT. Elevated serum neopterin levels have been found in a number of disease processes, including sarcoidosis, systemic lupus erythematosus, graft rejection, tuberculosis, and bacterial and viral infections, likely reflecting the inflammatory response in each of these diseases [Eklund and Blaschke, 1986;Woloszczuk et al, 1986;Lim et al, 1994;Hamerlinck, 1999;Mohamed et al, 2001]. Thus, high levels of serum neopterin could reflect an acute infection or an ongoing chronic inflammatory response other than from CBD.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…That study did not compare serum neopterin to the blood BeLPT. Elevated serum neopterin levels have been found in a number of disease processes, including sarcoidosis, systemic lupus erythematosus, graft rejection, tuberculosis, and bacterial and viral infections, likely reflecting the inflammatory response in each of these diseases [Eklund and Blaschke, 1986;Woloszczuk et al, 1986;Lim et al, 1994;Hamerlinck, 1999;Mohamed et al, 2001]. Thus, high levels of serum neopterin could reflect an acute infection or an ongoing chronic inflammatory response other than from CBD.…”
Section: Discussionmentioning
confidence: 94%
“…Numerous studies have found associations between serum and urine neopterin levels and other inflammatory disease processes, including sarcoidosis [Eklund and Blaschke, 1986;Prior et al, 1988], SLE [Lim et al, 1994], rheumatoid arthritis [Altindag et al, 1998], and graft rejection in transplant patients [Woloszczuk et al, 1986]. In sarcoidosis, serum and urinary neopterin levels have been primarily associated with chest radiographic stage and lymphocytic alveolitis [Eklund and Blaschke, 1986;Blaschke et al, 1988;Prior et al, 1988].…”
Section: Discussionmentioning
confidence: 98%
“…Using RIA and HPLC techniques, these urine samples were analyzed for cortisol as well as neopterin, an indicator of cellular immune activity and often used for serial determination of SLE activity [3]. Twice each day, the patients filled out questionnaires regarding their emotional state, perceived SLE activity and lifestyle factors (e.g.…”
mentioning
confidence: 99%
“…Autoregressive models have also been successfully used to describe on-line time series from intensive care bedside monitors [8]. Clinical investigations with autoregressive models into therapeutic effects have recently been reported from the fields of cardiology [10] rheumatology [17] neurology [18], psychiatry [19], and nursing research [20].…”
Section: Introductionmentioning
confidence: 99%